Better left unsent : a novel - Louis, Lia (Emily Bestler Books, Atria, 2024)
A woman who uses her email "drafts" folder to pen unsent sarcastic replies to her boss, difficult truths to her friends and love declarations to an engaged man must face all her repressed feelings when they all get sent.